Increased Knowledge of Lighting Installation, Hazards, And Electricity Use in Students of Kartika XIX-2 Junior High School Bandung - Siti Saodah; Ahmad Deni M; Ali Mashar; Aceng Daud; I Made Wiwit; Bella Eliana (Institut Teknologi Nasional, Bandung, 2023)
This community service proposed an introduction to electrical installation systems and electrical security systems for households in accordance with PUIL 2011 standards and international standards that could be applicable to students of Kartika XIX-2 Junior High School Bandung in the form of workshops. From this activity, it is expected that a good relationship will be established between the Community Service Team (P2M) of the Polban Energy Conversion Engineering (JTKE) and partners so that the knowledge transfer process can be carried out continuously. Moreover, it is also expected that partners will get benefits and social impacts, as follows; increasing insight to the importance of good and correct electrical installation knowledge in accordance with PUIL 2011, fostering safe behavior/habits when performing electrical installation work, as well as gaining basic knowledge of electrical installation work that can be used to obtain a certificate of electrical installation expertise.